Infodemiology of Crohn’s disease and Ulcerative colitis using Google Trends – an approach to investigate patient needs - Keller, Ronald; Fusco, Stefano; Stange, Eduard F.; Malek, Nisar P.; Wehkamp, Jan; Klag, Thomas (Zeitschrift für Gastroenterologie, 2020)
Introduction Inflammatory bowel diseases (IBD) highly affect quality of life. The course of disease and success of treatment are variable. These factors result in a high number of psychiatric comorbidities with patients requiring extensive medical consultation or additional psychotherapy. Unfortunately, time is often limited in daily clinical care, which leaves patients not feeling sufficiently informed about their disease. Patients often compensate by searching the internet, with possibly harmful information. We aim to identify information gaps to allow a more complete education of patients.Methods We analyzed the internet search behavior using the key words [Morbus Crohn] (CD) and [Colitis ulcerosa] (UC) using Google Trends. In addition, we investigated which websites are the first hits on Google, as those are most likely visited by patients.Results Symptoms, nutrition and therapy are central topics for persons interested in IBD. The searches concerning symptoms or therapies do not match the actual incidence or prevalence of comorbidities as well as the more commonly used therapies or established nutritional recommendations. We found a distinct impact of well-known personalities on disease related searches. The first suggested websites on google showed great heterogeneity of responsible publishers, often with possible conflict of interests. In line with those observations, quality of website content is highly heterogeneous.Conclusion This study showed a need of information concerning symptoms, nutrition and therapy that should be considered during patient education. Since time in physician patient dialogue is short it may be helpful to further evaluate websites independently in order to give recommendations of websites offering reliable information.
Keywords: Inflammatory bowel disease; Ulcerative colitis; Crohn’s disease